Epizootogical aspects of avian influenza prevention and control strategy in modern Russia - M. S. Volkov; V. N. Irza; A. V. Varkentin; A. S. Starova (Ветеринария сегодня)
The paper is devoted to wide spread of avian influenza virus in the world and the disease prevention and control in Russia. It is necessary to monitor efficacy of inactivated vaccines against avian influenza caused by the currently circulating epizootic strains due to the virus evolution and variability. Reassortment of influenza A virus poses a serious threat to effectiveness of vaccination as an alternative to drastic measures. The message of the paper is to demonstrate how to better meet new challenges from the perspective of time.